PENGARUH PRODUCT PLACEMENT TERHADAP PURCHASE INTENTION DENGAN BRAND AWARENESS SEBAGAI VARIABEL MEDIASI (STUDI EMPIRIS RESTORAN GOOBNE DALAM DRAMAKOREA “BUSINESS PROPOSAL”) - Rudy Vernando Silalahi; Yuvi Angel (Faculty of Economics and Business Universitas Pelita Harapan, 2023)
There is a phenomenon where someone just knows Goobne after watching the Korean drama